Conceptual Perspectives: Bacterial Antimicrobial Peptide Induction as a Novel Strategy for Symbiosis with the Human Host - Ghosh, Santosh K.; Feng, Zhimin; Fujioka, Hisashi; Lux, Renate; McCormick, Thomas S.; Weinberg, Aaron (Frontiers in Microbiology, 2018)
Human beta defensins (hBDs) are small cationic peptides, expressed in mucosal epithelia and important agents of innate immunity, act as antimicrobial and chemotactic agents at mucosal barriers. In this perspective, we present evidence supporting a novel strategy by which the oral bacterium Fusobacterium nucleatum induces hBDs and other antimicrobial peptides (AMPs) in normal human oral epithelial cells and thereby protects them from other microbial pathogens. The findings stress (1) the physiological importance of hBDs, (2) that this strategy may be a mechanism that contributes to homeostasis and health in body sites constantly challenged with bacteria and (3) that novel properties identified in commensal bacteria could, one day, be harnessed as new probiotic strategies to combat colonization of opportunistic pathogens. With that in mind, we highlight and review the discovery and characterization of a novel lipo-protein, FAD-I (Fusobacterium Associated Defensin Inducer) associated with the outer membrane of F. nucleatum that may act as a homeostatic agent by activating endogenous AMPs to re-equilibrate a dysregulated microenvironment. FAD-I has the potential to reduce dysbiosis-driven diseases at a time when resistance to antibiotics is increasing. We therefore postulate that FAD-I may offer a new paradigm in immunoregulatory therapeutics to bolster host innate defense of vulnerable mucosae, while maintaining physiologically responsive states of inflammation.